High gain fabry-perot antenna with broadband low radar cross section and deflected beam radiation for stealth platforms / Hassan Umair - Hassan , Umair (2021)
As stealth technology has stood its ground for military/defense deterrence, it has become growingly important to develop antennas compatible with low-observable platforms. Antennas can be huge source of radar backscatter, thereby increasing radar signature of the platform on which it is mounted. This consequently compromises the target’s stealth property. To counter this, many techniques have been adopted to reduce antenna radar cross section (RCS), which include shaping, radar absorbing material (RAM) coatings, frequency selective surface (FSS) radomes/ground-planes, and implementing absorptive electromagnetic band gap (EBG) structures or perfect metamaterial absorbers. In most of these cases, antenna radiation is either deteriorated, or just remains intact. To this end, partially reflecting surfaces (PRSs) integrated with absorptive FSSs in a Fabry-Perot (FP) cavity configuration have been employed above patch antennas, which not only achieve wideband absorption of radar waves, but also enhance antenna’s radiated gain. However, so far, the adoption of phase gradient metasurfaces (PGM) with the absorptive/scattering surfaces, to achieve not only low RCS and high radiated gain, but also antenna beam deflection, has not been explored yet. It can find useful applications such as in side-looking airborne radars (SLARs), satellite communication platforms, base station antennas, pattern decorrelated multiple-input multiple-output (MIMO) antenna, or any military application requiring off-the-horizon communication. In view of this, three FP antennas have been presented in this thesis, realizing following functionalities all in parallel: (1) wideband low monostatic RCS, (2) antenna gain enhancement, and (3) antenna beam deflection. As first objective of the thesis, an FP antenna has been designed employing an absorptive FSS integrated with a dual sided phase gradated PRS. The achieved wideband absorptivity ranges from 5.8-16 GHz (93.57%), for arbitrary polarizations. Peak gain is 11.5 dB at 6.6 GHz, with tilt angle of 13° in the elevation plane. Cavity height is λ/2. As second objective, same configuration has been adopted but with modified gradient implementation. Advantages achieved are the increase of the tilt angle to 32°, and the reduction of cavity height to λ/4. Wideband RCS reduction, from 4-16 GHz (120%), has been achieved. Peak gain is 9.4 dB at 6 GHz. Finally, in third objective, to achieve RCS reduction, instead of adopting resistive FSS, artificial magnetic conductor (AMC) based approach has been implemented leveraging reflection phase cancellation principle over a wideband. Advantage over previous approaches is the lesser complexity and cost, as no resistor soldering/stuffing is required. The checkerboard AMC surface has been integrated with PGM, achieving wideband RCS reduction from 4-13 GHz (105.8%), peak gain of 12 dB at 7 GHz, and beam deflection of 60°. Cavity height is 0.33λ. Afterwards, the antenna’s modified version has also been presented, in which the AMC interfaces of destructive interference have been ignored in one of the principal axes (y-axis). The result is a 41% reduction of cavity’s aperture size; however, the RCS reduction bandwidth, which is still wide, is asymmetric for orthogonal polarizations of the incident wave. For the three objectives, detailed simulation/measurement results have been presented, along with performance comparisons with previous literature.